Proceedings of the 2nd International Conference on Electrical and Electronic Engineering (EEE 2019) 2019
DOI: 10.2991/eee-19.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Congestion Detecting by VANETs

Abstract: Accurate traffic congestion detection methods are needed urgently to improve road traffic pressure and congestion, especially in metropolitan areas. This paper proposes TraD-VANET, a new road traffic detection system that employs RFID-based active vehicle positioning and vehicular adhoc networks (VANETs) to detect traffic congestion dynamically. The results can be used to making road traffic flow more fluent and effective. To validate the performance of TraD-VANET, we ran a simulation compared with cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Fuzzy logic is also a popular mechanism used in VANET. Besides been utilized in detecting traffic congestion as in COTEC [19], CARTIM [20], Rui et.al [21], and most recently Wang et.al [22] and TraD-VANET [23] it is also implemented in localization, clustering, beaconing dissemination, aggregation, and other processes in VANET [24][25][26][27]. The fuzzy mechanism detects traffic congestion based on vehicular speed and traffic density.…”
Section: Fuzzy Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuzzy logic is also a popular mechanism used in VANET. Besides been utilized in detecting traffic congestion as in COTEC [19], CARTIM [20], Rui et.al [21], and most recently Wang et.al [22] and TraD-VANET [23] it is also implemented in localization, clustering, beaconing dissemination, aggregation, and other processes in VANET [24][25][26][27]. The fuzzy mechanism detects traffic congestion based on vehicular speed and traffic density.…”
Section: Fuzzy Logicmentioning
confidence: 99%
“…The classification is accomplished by a majority vote of the most common of the predominant class known among its k nearest neighbors. It is also characterized as a lazy algorithm, defined as having less ability and is labor intensive when dealing with large datasets [22,23]. The operation of this algorithm is based on comparing a newly received record with the training records and finding training records identical to it.…”
Section: K-nn Classifiermentioning
confidence: 99%
“…Even though they noticed a higher number of drivers reducing their speed, they explained that as a chain reaction where one vehicle braked and forced the following vehicles to brake or change lanes in order to avoid collisions. More recent articles investigate the exploitation of vehicular ad-hoc network (VANET) architecture to overcome the problem of congested metropolitan areas [28][29][30]. Conducted studies showed that such systems can effectively reduce traffic level inside cities, exploiting inter-communication among vehicles and supporting infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…This method alleviated the overload of the communication channel in [12], however, the vehicles that were responsible for collecting and processing traffic information would cause additional channel overhead. A method for the automatic clustering of vehicles was proposed in [14], which used a cluster head node to report the current position and speed information of the vehicle in clusters, to accomplish road traffic congestion detection. This method could reduce the amount of data traffic and avoid the problem of channel overload by aggregating the messages in a cluster, but the detection accuracy was low.…”
Section: Introductionmentioning
confidence: 99%